Analysis The Use Of Qawaid Fiqhiyyah In The Decree Of The Fatwa Of Aceh Islamic Scholar Consultative Assembly (MPU) - Liantha Adam Nasution (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
Aceh is a province that has privileges compared to other regions in Indonesia, the privilege of Aceh is to be able to carry out the aspirations and dreams of the Acehnese people so that they carry out Islamic Sharia properly and are protected by state laws that will create a civil society based on the Kaffah Islamic Sharia. In compiling the Rules and Implementation based on Islamic Shari'ah, the Acehnese government established an institution that houses Aceh's Islmic scholars and has the authority to provide Islamic legal considerations in drafting Qanun and legal rules in Aceh, the institution is Aceh Islamic Scholar Consultative Assembly (MPU). The study uses a normative approach that focuses on the study of laws/regulations issued by Aceh Islamic Scholar Consultative Assembly by looking directly at the rules and classifying Fatwa, Ijma’a, Qiyas, and Aceh Islamic scholar’s views which will be deductively concluded. Based on the analysis of the legal products issued by Aceh Islamic Scholar Consultative Assembly, it is clear that the application of Qawaid Fiqh is considered and becomes a source of rules in decisions relating to Contemporary but the use of Qawaid Fqih in several Fatwas and Decrees is not clearly stated in the Qawaid Fiqh used.Keywords: Qawaid Fiqih, Fatwa, Islamic Scholar Consultative Assembly